Increasing awareness and prompting HIV testing: Contributions of Amsterdam HIV Testing Week 2016. (October 2018) - den Daas, C; Meddens, EM; van Bergen, JEAM; de Bree, GJ; Hogewoning, AA; Brinkman, K; de Wit, JBF
We evaluated Amsterdam HIV Testing Week (HTW) 2016 regarding its primary goals of raising awareness and prompting HIV testing. Participating services offered free, anonymous HIV testing, with a focus on reaching men who have sex with men (MSM) and people with a non-western migration background. Sociodemographic characteristics, HIV testing history, intention to test regularly, beliefs about personal risk and severity of HIV, and perceived social norms regarding HIV testing and people living with HIV were assessed among all who tested. A community quick scan assessed awareness of Amsterdam HTW 2016 and attitudes and intentions regarding HIV testing. Of 806 people tested, 59.6% (405/679) belonged to key populations. None tested HIV-positive and 37.6% intended to test regularly in the future. The community quick scan found moderate awareness of Amsterdam HTW 2016. Awareness was highest among recent testers and HIV-positive MSM and not associated with HIV testing attitudes and intentions. People tested during Amsterdam HTW 2016 were from key populations and/or were not (adequately) reached via traditional testing approaches. The contribution of the Amsterdam HTW approach to raising awareness and prompting HIV testing in key populations may benefit from focusing on HIV-negative individuals who have not been tested recently.